Shabu ; Spolarium ; Martin [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Probe examines the "poor man's cocaine" ; restoration of Juan Luna's masterpiece which causes a controversy over the methods and the credentials of the restorer ; and interview with Martin Nievera about his singing carrer and his family.